Immune biomarkers for prognosis and prediction of responses to immune checkpoint blockade in cutaneous melanoma. (3rd August 2017) - Jacquelot, Nicolas; Pitt, Jonathan M.; Enot, David P.; Roberti, Maria Paula; Duong, Connie P. M.; Rusakiewicz, Sylvie; Eggermont, Alexander M.; Zitvogel, Laurence
ABSTRACT: Existing clinical, anatomopathological and molecular biomarkers fail to reliably predict the prognosis of cutaneous melanoma. Biomarkers for determining which patients receive adjuvant therapies are needed. The emergence of new technologies and the discovery of new immune populations with different prognostic values allow the immune network in the tumor to be better understood. Importantly, new molecules identified and expressed by immune cells have been shown to reduce the antitumor immune efficacy of therapies, prompting researchers to develop antibodies targeting these so-called "immune checkpoints", which have now entered the oncotherapeutic armamentarium.